2020
DOI: 10.1002/elps.202000084
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances of green pretreatment techniques for quality control of natural products

Abstract: A few advancing technologies for natural product analysis have been widely proposed, which focus on decreasing energy consumption and developing an environmentally sustainable manner. These green sample pretreatment and analysis methods following the green Analytical Chemistry (GAC) criteria have the advantage of improving the strategy of chemical analyses, promoting sustainable development to analytical laboratories, and reducing the negative effects of analysis experiments on the environment. A few minimized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 106 publications
0
6
0
Order By: Relevance
“…69 Eliminating interfering species, extracting analytes, and increasing the concentration of the analyte to improve the final signal are the main objectives of the pre-treatment procedure. 70 We carried out an in-depth review of the different techniques, particularly recent trends, employed in laboratories for antidepressant extraction from various biological matrices.…”
Section: Discussionmentioning
confidence: 99%
“…69 Eliminating interfering species, extracting analytes, and increasing the concentration of the analyte to improve the final signal are the main objectives of the pre-treatment procedure. 70 We carried out an in-depth review of the different techniques, particularly recent trends, employed in laboratories for antidepressant extraction from various biological matrices.…”
Section: Discussionmentioning
confidence: 99%
“…ESI-MS spectra were obtained on the Agilent 6500 series Q-TOF mass spectrometer. Using deuterated methanol as a solvent, the 1 H and 13 C nuclear magnetic resonance (NMR) spectroscopic data were recorded on the Bruker Avance NMR spectrometer at 600 MHz. Multimode Microplate Reader was purchased from Molecular Devices (Shanghai, China), while the BioMajesty ® JCA-BM6010/C was supplied by the Sysmex (Wuxi, China).…”
Section: Apparatus and Reagentsmentioning
confidence: 99%
“…The comparison with the ch matogram of the crude extract (Figure 9A) demonstrated that Fr31 was indeed the m functional compound present in the ethyl acetate extraction of D. heterophyllum. Its str ture was further studied by ESI-MS, 1 H, and 13 C NMR spectral analyses and data w documented and identified in comparison with the present information in the literatu Below, we list all spectra of the original spectra records, while the raw spectra are sho in the supporting materials (Figures S1-S3). Our results proved that the key compon isolated from the ethyl acetate extraction of D. heterophyllum was the rosmarinic acid.…”
Section: Purity Analysis and Structural Characterization Of The Targe...mentioning
confidence: 99%
See 2 more Smart Citations